Experiencias sexuales en la etapa del enamoramiento de los estudiantes de la carrera de Psicopedagogía de la Universidad Nacional de Chimborazo - Guevara Sosa, Guisselle Nataly (2022)
The development of this research aims to determine the sexual experiences in the stage of falling in love in the students of the Psychopedagogy career at the National University of Chimborazo; falling in love is a feeling that human beings experience at any stage of life, it appears when we feel a strong attraction to another individual of the opposite sex or of the same sex; the affective experience of sexuality encompasses everything that allows human beings to seek loving contact or sexual pleasure with another person. The methodology used for the development of the research has a mixed approach, with a non-experimental design, the type of research is, according to its scope, it is descriptive, for its objective it is basic, for the place of field and bibliography and for the time it is transversal. . The study population was the students of the Psychopedagogy career, taking as an intentional sample at the fifth, sixth and seventh semester levels, that is, a total of 106 students; the technique that was used was the survey, as an instrument the ADHOC questionnaire, made up of twenty closed questions from which the data collection was carried out, which were interpreted by means of statistical tables and charts. Concluding that the most common sexual relations of the students of the Psychopedagogy career, is based on respect, in such a way that they feel safe and are not ashamed to show their desires or sexual behaviors, they have the freedom to take the initiative to have sexual intercourse with your partner. In addition, there is little concern for maintaining an active and satisfactory sexual life, they mention that having sex with their partners also leads to stronger feelings towards the other person, taking into account that sexual relations are not only a biological necessity, but also emotional which needs to be satisfied. Keywords: Sexual Experiences, Infatuation, Sexual Behavior